“TEMANTA”KELOMPOK PENDAMPING TEMAN SEBAYA DALAM UPAYA PENCEGAHAN KEHAMILAN PRANIKAH REMAJA - Jamir, A.Fatimah; lindriani, lindriani; Rosdiana, Rosdiana (Universitas Mataram, 2024)
Premarital pregnancy is a pregnancy that is generally unplanned and gives rise to feelings of guilt, sin and shame in teenagers who experience it, coupled with social sanctions from society against pregnancy and the birth of children without marriage. Early pregnancy increases the mortality rate for babies and mothers under 18 years of age. The reason is, a young teenager is at greater risk of dying during pregnancy and childbirth than women aged 20 years and over. The aim of this community service is to form a